Characteristics and Risk Factors of Patients with Acute Ischemic Stroke in Dr. Hasan Sadikin General Hospital Bandung, Indonesia - Nesyia Tara Restikasari; Uni Gamayani; Lisda Amalia; Sofiati Dian; Aih Cahyani (Althea Medical Journal, 2022)
Background: Stroke is the second most common cause of death globally and the third most common cause of disability. The prevalence of stroke is increasing despite managing various stroke risk factors that have improved considerably. Ischemic stroke is the most prevalent type, and about 90% of stroke events are attributable to modifiable risk factors. This study aimed to explore the characteristics and risk factors of patients with acute ischemic stroke in Dr. Hasan Sadikin General Hospital.Methods: A descriptive cross-sectional study was conducted retrospectively in October 2020, using a total sampling method on medical records of acute ischemic stroke patients in Dr. Hasan Sadikin General Hospital year 2019. Medical records with incomplete and missing data were excluded. Demographic and known risk factors data were collected and presented in the table.Results: Of the 355 subjects, male patients (n=69, 76.7%) were predominant, with the age range of 55–64 years old (36.1%). The majority of the subjects had an ischemic stroke of large-artery atherosclerosis (68.2%) with carotid system involvement (93.2%). As much as 305 subjects (85.9%) had hypertension as the risk factor, followed by dyslipidemia (47.3%), heart disease (39.4%), previous stroke history (33.8%), smoking (25.6%), diabetes mellitus (24.5%), hyperuricemia (12.1%), and blood disorders (2.3%).Conclusions: Males in the older age group have a higher risk of getting acute ischemic stroke with ischemic stroke of large-artery atherosclerosis and carotid system involvement, and hypertension has the highest prevalence.